2015
DOI: 10.1177/1526602815575260
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Hybrid Sutureless Anastomosis on Porcelain Aorta

Abstract: This sutureless anastomosis technique seems safe and feasible and represents a valid alternative to standard surgical approaches in cases of heavy and circumferentially calcified infrarenal aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…In 2008, Lachat et al 12 introduced the Viabahn Open Revascularization TEChnique (VORTEC), in which a stent graft is used to form a sutureless anastomosis in renal revascularization surgery. Since then, several authors (Bonvini et al, 13 Segers et al, 14,15 Donas et al, 16 Papadimitriou et al 17 ) have attempted to use this technique in aortic surgery. According to this technique, the aorta is punctured and a guidewire is positioned in the aorta.…”
Section: Aad Typesmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2008, Lachat et al 12 introduced the Viabahn Open Revascularization TEChnique (VORTEC), in which a stent graft is used to form a sutureless anastomosis in renal revascularization surgery. Since then, several authors (Bonvini et al, 13 Segers et al, 14,15 Donas et al, 16 Papadimitriou et al 17 ) have attempted to use this technique in aortic surgery. According to this technique, the aorta is punctured and a guidewire is positioned in the aorta.…”
Section: Aad Typesmentioning
confidence: 99%
“…A total of 41 studies 10,11,13,14,[16][17][18][19] were identified that reported outcomes for the use of AADs during surgery for thoracic and abdominal aortic reconstruction (Supplementary Tables I and II, online only). The meta-analysis included 27 studies with 50 cohorts, incorporating 1260 patients (Supplementary Table I, online only).…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Sutureless anastomoses with covered self-expanding stents such as the VORTEC (Viabahn Open Revascularisation TEChnique) have been described for several anatomic areas with technical success [3,4,5]. The Gore hybrid vascular graft (GHVG), to our knowledge currently the only available device with these features, represents the natural evolution of these techniques.…”
Section: Commentmentioning
confidence: 99%